Abnormal symptoms in micropropagation and strategies to overcome - My Ngan, Ha Thi; Thanh Tung, Hoang; Van Le, Bui; Tan Nhut, Duong (Vietnam Journal of Biotechnology, 2020)
Nowaday, plant cell, tissue and organ culture has become a standard and popular propagation method for many crops including ornamental plants, medicinal plants, fruit trees and green vegetables. The advantage of this method is that it can generate a huge number of genetically identical seedlings, effectively control the pathogenicity in order to produce disease-free plants, become a tool for conservation and development of genetic sources and support study of physiological characteristics of plants. However, this method still has some limitations such as abnormal physiological morphology and anatomical structure; necrosis and deformities plants; stomata loss of function, etc. These abnormalities have great impacts on shoot multiplication as well as the growth and development of the plants after transplanted from the culture vessels to the nursery stage. The components of in vitro culture conditions such as culture system, composition and content of nutrients, plant growth regulators used in the culture medium, light, temperature and humidity, age and origin of explants, etc., are the main causes of the abnormalities. Therefore, optimization of culture system to improve the quality of seedlings has always been one of the main targets of commercial micropropagation. In this review, we focused on some frequently abnormal symptoms in micro - propagation such as vitrification, yellowing and abscission of leaves; microbial contamination; necrosis of shoot-tip, roots and tissues culture; browning of explants and medium culture and other restrictions. More over, this report showed some the effective solutions to overcome these abnormal phenomena.